SLOPE STABILITY ANALYSIS OF DISPOSAL AREA WITH GROUNDWATER TABLE AND MATERIAL DENSITY VARIATIONS USING THE BISHOP METHOD - Oziana, Deea Rizki; Ramadhandi, Farhan; Hulwani, Zati; Harisman, Hendra; Alam, Pocut Nurul (Jurnal Sains dan Teknologi Reaksi, 2025)
Slope stability is crucial in mining activities, particularly in disposal areas composed of loose materials with varying geotechnical conditions. Groundwater level and material density are significant factors that influence slope stability. This study aims to analyze the effects of groundwater level variations and material density on the safety factor of disposal slopes using the Bishop method within the GeoStudio SLOPE/W software framework. The research was conducted in a coal mine disposal area, divided into three cross-sections: A–A’, B–B’, and C–C’. Simulations were performed under three conditions: unsaturated (normal), saturated (due to intense rainfall), and threshold (the maximum critical condition still considered stable). The results show that rising groundwater levels significantly reduce the slope’s safety factor (SF). Under saturated conditions, the SF for all three cross-sections dropped below 1.0, indicating unstable slopes. Specifically, the SF declined from 1.15 to 0.72 for section A–A’, from 1.16 to 0.55 for B–B’, and from 1.18 to 0.81 for C–C’. In contrast, an increase in wet material density led to only moderate reductions in SF, with values remaining above 1.0. The combination of high groundwater levels and increased material density poses a critical risk factor for potential slope failure. Continuous hydrogeological monitoring is therefore essential to ensure the long-term stability of mine disposal areas. Keywords: slope stability, groundwater table, material density